2004
DOI: 10.1038/sj.cdd.4401507
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of osteosarcoma cells to death receptor-mediated apoptosis by HDAC inhibitors through downregulation of cellular FLIP

Abstract: Fas-mediated apoptosis plays an important role in elimination of tumor cells in vivo, but some tumor-derived cells are resistant to this mechanism. Here, we show that treatment with the histone deacetylase (HDAC) inhibitor FR901228 renders Fas-resistant osteosarcoma cell lines sensitive to Fas-mediated apoptosis by downregulating expression of cellular FLIP (cellular FLICE-inhibitory protein), an inhibitor of Fas-mediated activation of caspase-8. Moreover, sensitization to Fas-mediated apoptosis was also induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 38 publications
4
65
2
Order By: Relevance
“…We and others have reported that chemical and genetic inhibition of HDACs leads to decreased expression of FLIP mRNA (36)(37)(38)(39)(40)(41)(42)(43). However, the mechanism by which inhibiting HDACs decreases FLIP expression is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have reported that chemical and genetic inhibition of HDACs leads to decreased expression of FLIP mRNA (36)(37)(38)(39)(40)(41)(42)(43). However, the mechanism by which inhibiting HDACs decreases FLIP expression is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…In myocytes, Hopx can also interact with histone deacetylase 2 and recruits it to SRF-Hopx complexes [51]. Interestingly, histone deacetylase inhibitors have been reported to activate apoptotic pathways including Fas-mediated apoptosis [52][53][54][55] and exhibit therapeutic potential in the treatment of cancer [56,57] and inflammatory diseases [58,59]. In skeletal muscle cells, Hopx is expressed as well, but acts independently of SRF and mostly activates transcription of the target genes [60].…”
Section: Discussionmentioning
confidence: 99%
“…29 FK228 also decreases expression of FLICE inhibitory protein (FLIP) in osteosarcoma and leukemic cells. 21,30 Thus, expression of many apoptosis-related molecules could be modified by HDAC inhibitors. However, we found that FK228 treatment did not change Bcl-2 and Bcl-XL expression and barely affected expression of Bid, Bad, Bim and BAX in SAS and HSC2 cells, suggesting their marginal contribution in FK228 or CBHA-induced apoptosis, though we cannot exclude the possibility that they are somehow involved in the event.…”
Section: Discussionmentioning
confidence: 99%
“…18 In contrast, HDAC inhibitors somehow increase degradation of several apoptosis-related proteins, such as p53, bcr-abl and cellular FADD-like interleukin 1-bconverting enzyme (FLICE)-inhibitory protein FLIP. [19][20][21] However, it is unlikely that these molecules play pivotal roles in the broad spectrum of HDAC inhibitor-induced apoptosis. A recent report shows that HDAC inhibitors increase acetylation of Ku70 and abolish its ability to suppress Bax-mediated apoptosis.…”
Section: Introductionmentioning
confidence: 99%